Effective Character Education for Children: Insights from Family-Based Approaches in Indonesia - Khan, Rosa Imani (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
As the core environment most familiar to children, the family contributes to the awareness, cultivation, and development of children's character. The internalization of family character values ​​in children will tend to be more inherent than the results of character cultivation at school. This research aims to describe character education for children based on the family environment. This research was conducted using qualitative descriptive methods. The necessary data was collected through literature study and then interpreted to describe character education for children carried out by parents in the family environment. Character education for children based on the family environment is an effort made by parents in the family to educate children to have a character that is in line with ethical values. Character education must start from the family to form a noble personality. The parenting style in the family is closely related to forming the child's character. This character will be carried over until the child becomes an adult and married. The family does have a vital role in building a child's character, but children also have the right to choose their world. If a child's actions are wrong, the family must provide guidance, direction, example, and practice instilling good moral values ​​in the child. Every family must understand and be aware that the child's character is very dependent on the character education process in the family.